DISTRIBUSI SPASIAL DENSITAS CAKRAM BERUKURAN SAMA DALAM PEMODELAN PEMBENTUKAN ASTEROID - Sparisoma Viridi; Budi Dermawan (Program Studi Fisika Universitas Negeri Jakarta, 2017)
Several two-dimension particles in the form of a disk, which only interact through gravitational force and normal force, are simulated. Assumed that there are only two values of particle density (same diameter but different mass). Simulation are conducted until particles position are slightly constant. It is obtained that density is varied radially, decreasing with an increase of radial position, and nearly isotropic angularly in final condition. It has been simulated N = 64 particles with mass ratio mA/mB = 0.25 for 944 s simulation time. Keywords: asteroid forming, granular material, density distribution, binary mixture